2006
DOI: 10.1207/s15324826an1304_8
|View full text |Cite
|
Sign up to set email alerts
|

GRAND ROUNDS: Topographical Heading Disorientation - A Case Study

Abstract: We report the case of a patient with selective topographic orientation deficits in both familiar and novel environments after bilateral medial occipital infarctions. Extensive neuropsychological assessment revealed intact functioning in all other cognitive domains. The findings are interpreted in terms of a dissociation between the retrosplenial posterior cingulate and the superior parietal lobule in the right hemisphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…For example, one patient suddenly became lost while returning home from work: “He could recognize buildings and the landscape and therefore understand where he was, but the landmarks that he recognized did not provoke directional information about any other places with respect to those landmarks. Consequently, he could not determine which direction to proceed.” [71] Such navigational difficulties have been reported after lesions affecting the right hemisphere [70,72,74,75], left hemisphere [71,75,77], both hemispheres [76], and retrosplenial white matter [73]. Interestingly, these problems often clear up after a few months with unilateral damage [70,75] but not bilateral damage [76], possibly because the undamaged hemisphere begins to compensate [8].…”
Section: The Retrosplenial Complex (Rsc)mentioning
confidence: 99%
“…For example, one patient suddenly became lost while returning home from work: “He could recognize buildings and the landscape and therefore understand where he was, but the landmarks that he recognized did not provoke directional information about any other places with respect to those landmarks. Consequently, he could not determine which direction to proceed.” [71] Such navigational difficulties have been reported after lesions affecting the right hemisphere [70,72,74,75], left hemisphere [71,75,77], both hemispheres [76], and retrosplenial white matter [73]. Interestingly, these problems often clear up after a few months with unilateral damage [70,75] but not bilateral damage [76], possibly because the undamaged hemisphere begins to compensate [8].…”
Section: The Retrosplenial Complex (Rsc)mentioning
confidence: 99%
“…In general, RSP lesions impair performance in these tasks provided that the lesions are large, extending throughout the rostral-caudal extent of RSP (Vann & Aggleton, 2004; Vann et al, 2003). Navigational difficulties are also reported after the RSP is damaged by stroke in humans (Cammalleri et al, 1996; Takahashi et al, 1997; Aguirre & D’Esposito, 1999; Maguire, 2001; Greene et al, 2006; Osawa et al, 2008), and functional neuroimaging studies frequently demonstrate strong bilateral RSP activation in tasks involving spatial problem solving (Epstein et al, 2007; Iaria et al, 2007; Maguire, 2001; Park & Chun, 2009; Wolbers & Büchel, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…A striking feature of the spatial deficits following RSP damage in humans is the report that patients suffer from what has been described as heading (or topographic) disorientation (Cammalleri et al, 1996; Aguirre & D’Esposito, 1999; Greene et al, 2006; Ino et al, 2007). These patients are generally unable to orient with respect to available environmental landmarks and set a course to where they want to go, even though they are capable of recognizing the landmarks and are capable of describing the intended destination.…”
Section: Introductionmentioning
confidence: 99%
“…Previous lesion studies have shown bilateral occipital lobe, hippocampus, and parahippocampal gyrus or retrosplenium involvements and visuospatial learning and memory impairments (Habib & Sirigu, 1987;Maguire, 1997;Epstein, Harris, Stanley, & Kanwisher, 1999;Takahashi & Kawamura, 2002;Greene et al, 2006). A review of the literature (PubMed, EBSCO, Springer, OVID, Elsevier, ProQuest, Blackwell-Synergy) did not reveal information reporting a patient having difficulty in learning of new routes after TBI.…”
Section: Discussionmentioning
confidence: 87%
“…The output of primary visual areas is transmitted to the inferiomedial temporal cortex, in which the meaning of the stimulus is decoded, and to the posterior parietal cortex, in which its spatial coordinates are analyzed. In humans, the nondominant hemisphere has the prominent role in analysis of spatial properties of objects (Fisher, 1982;Habib & Sirigu, 1987;Vighetto et al, 1985;Funakawa, Mukai, Terao, Kawashima, & Mori, 1994;Rainville, Giroire, Periot, Cuny, & Mazaux, 2003;Greene, Donders, & Thoits, 2006). Route learning similarly involves two main processes related to environmental information: the representation of new visual landmarks, and the structuring of a spatial relationship among them.…”
Section: Introductionmentioning
confidence: 99%